The Euro Crisis and Economic Growth: A Novel Counterfactual Approach - Alessio Terzi (Center for Economic Studies and ifo Institute (CESifo), 2019)
Macroeconomic adjustment in the euro area periphery was more recessionary than pre-crisis imbalances would have warranted. To make this claim, this paper uses a Propensity Score Matching Model to produce counterfactuals for the Eurozone crisis countries (Greece, Portugal, Ireland, Cyprus, Spain) based on over 200 past macroeconomic adjustment episodes between 1960-2010 worldwide. At its trough, between 2010 and 2015 per capita GDP had contracted on average 11 percentage points more in the Eurozone periphery than in the standard counterfactual scenario. These results are not dictated by any specific country experience, are robust to a battery of alternative counterfactual definitions, and stand confirmed when using a parametric dynamic panel regression model to account more thoroughly for the business cycle. Zooming in on the potential causes, the lack of an independent monetary policy, while having contributed to a deeper recession, does not fully explain the Eurozone's specificity, which is instead to be traced back to a sharper-than-expected contraction in investment and fiscal austerity due to high funding costs.
Keywords: E63; E65; F31; F32; F33; F36; F45; 330; macroeconomic adjustment; financial crisis; Eurozone; growth; propensity score matching